Application of MALDI-TOF mass spectrometry for study on fibrillar and oligomeric aggregates of alpha-synuclein - Severinovskaya, O.V.; Kovalska, V.B.; Losytskyy, M.Yu.; Cherepanov, V.V.; Subramaniam, V.; Yarmoluk, S.M. (Вiopolymers and Cell, 2014)
Aim. To study the -synuclein (ASN) aggregates of different structural origin, namely amyloid fibrils and spherical oligomers, in comparison with a native protein. Methods. MALDI TOF mass spectrometry and atomic for- ce microscopy (AFM). Results. The mass spectra of native and fibrillar ASN have similar character, i. e. they are characterized by the well pronounced peak of protein molecular ion, the low molecular weight associates, and rather low contain of fragmentation products. The spectrum of oligomeric aggregate is characterized by the high contain of fragmentation products, low intensity of protein molecular ion and the absence of peaks of associates. Conclusions. The difference between the spectra of fibrillar and oligomeric ASN could be explained, first, by the different content of the «residual» monomeric ASN and the protein degradation products in the studied samples, and, second, by the different structure-depended mechanisms of the protein degradation induced by the laser ionization. We suggested that the MALDI-TOF mass spectroscopy is a method useful for the investigation of ASN aggregation and characterization of its high order self-associates; besides, there is an interest in estimating the potency of the MALDI-TOF for the analysis of aggregation of various amyloidogenic proteins. Мета. Вивчення агрегатів альфа-синуклеїну (ASN) різного структурового походження, а саме – амілоїдних фібрил і сферичних олігомерів порівняно з нативним білком. Методи. MALDI-TOF мас-спектрометрія та атомно-силова мікроскопія (АFМ). Результати. Мас-спектри нативного і фібрилярного ASN мають подібний характер – для них характерні інтенсивний пік молекулярного іона білка, піки низькомолекулярних асоціатов та досить незначний вміст продуктів фрагментації білка. У той же час у спектрі олігомерних агрегатів спостерігаються висока концентрація продуктів фрагментації білка, низька інтенсивність молекулярного іона та відсутність піків самоасоціатів. Висновки. Різницю між спектрами фибрилярного та олігомерного ASN можна пояснити як наявністю у зразках «залишкового» ASN і продуктів деградації білка, так і різними структурово залежними механізмами руйнування цих двох видів агрегатів при лазерній десорбції/іонізації. MALDI-TOF мас-спектрометрію можна запропонувати як метод вивчення агрегації та аналізу високомолекулярних агрегатів ASN. Також представляє інтерес визначення ефективності цього методу для дослідження агрегатів різних амілоїдогенних білків. Цель. Изучение агрегатов альфа-синуклеина (ASN) различной структуры, а именно – амилоидных фибрилл и сферических олигомеров в сравнении с нативным белком. Методы. MALDI-TOF масс-спектрометрия и атомно-силовая микроскопия (АFМ). Результаты. Масс-спектры нативного и фибриллярного ASN имеют подобный характер – для них характерны интенсивный пик молекулярного иона белка, пики низкомолекулярных ассоциатов, а также достаточно незначительное содержание продуктов фрагментации белка. В то же время в спектре олигомерных агрегатов наблюдаются высокая концентрация продуктов фрагментации белка, молекулярный ион низкой интенсивности и отсутствие пиков ассоциатов белка. Выводы. Различие между спектрами фибриллярного и олигомерного ASN можно объяснить как содержанием «избытка» ASN и продуктов деградации белка, так и различными структурно-зависимыми механизмами разрушениями этих двух видов агрегатов при лазерной десорбции/ионизации. MALDI-TOF масс-спектрометрию можно предложить в качестве метода изучения агрегации и анализа высокомолекулярных агрегатов ASN. Также представляет интерес определение эффективности MALDI-TOF для исследования агрегатов различных амилоидогенных белков.